Comparative pharmacokinetics of low- and high-dose ticarcillin. - Guglielmo, B J (1986)
Certain antipseudomonal penicillins, such as mezlocillin, exhibit a nonlinear pharmacokinetic disposition with increasing doses. We evaluated the effect of a single low dose (50 mg/kg) compared with a high dose (80 mg/kg) on the pharmacokinetics of ticarcillin in a crossover trial of eight healthy volunteers. No significant alteration in plasma clearance (130.1 +/- 36.5 versus 120.5 +/- 38.0 ml/min), nonrenal clearance (36.5 +/- 8.4 versus 33.4 +/- 18.5 ml/min), or volume of distribution at steady state (12.8 +/- 3.5 versus 12.3 +/- 4.5 liters) was observed between the low- and high-dose regimens, respectively. The elimination half-life remained unchanged between the two doses (67.9 +/- 14.3 versus 68.0 +/- 12.2 min). Unlike other newer antipseudomonal penicillins, ticarcillin did not display dose-dependent pharmacokinetic behavior with the range of doses used in the clinical setting.